Cranial hypertrophic interstitial neuropathy. - Jordan, J E; Lane, B; Marks, M; Chang, Y; Weinberger, M (American Journal of Neuroradiology, 1992)
The authors describe a patient with complex cranial neuropathy caused by pathologically proved hypertrophic interstitial neuropathy. Plain and contrast-enhanced MR studies were performed prior to surgical exploration. Surgical complications caused the patient's death and a complete pathology study was done. Though nonspecific, MR proved helpful in determining the extent of disease and areas of anatomic involvement.